2004
DOI: 10.1017/s001216220400091x
|View full text |Cite
|
Sign up to set email alerts
|

Care provider assessment of intrathecal baclofen in children

Abstract: Intrathecal baclofen is used increasingly to manage severe spasticity in children. Before implanting the baclofen pump, care providers typically ask how it will benefit their child. The purpose of this study was to describe the perceptions of care providers about intrathecal baclofen for management of spasticity in 80 individuals (52 males, 28 females). The individuals were younger than 22 years at the time of implantation (mean age 11 years, SD 5 years; range 3 to 21 years). Participants had been implanted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 12 publications
5
52
0
1
Order By: Relevance
“…If focal treatment is ineffective and more general relief is indicated, insertion of a baclofen pump may be instituted for continuous intrathecal medication infusion. However, the inserted pump may interfere with the ability to ambulate and has inherent risks associated with placement (Gooch, Oberg, Grams, Ward, & Walker, 2004). Surgical interventions such as selective rhizotomy, tenotomy, or myotomy are reserved for failure of pharmacologic and physiotherapy management to achieve patient goals.…”
Section: Common Problems In Tbi Managementmentioning
confidence: 99%
“…If focal treatment is ineffective and more general relief is indicated, insertion of a baclofen pump may be instituted for continuous intrathecal medication infusion. However, the inserted pump may interfere with the ability to ambulate and has inherent risks associated with placement (Gooch, Oberg, Grams, Ward, & Walker, 2004). Surgical interventions such as selective rhizotomy, tenotomy, or myotomy are reserved for failure of pharmacologic and physiotherapy management to achieve patient goals.…”
Section: Common Problems In Tbi Managementmentioning
confidence: 99%
“…The use of ITB pumps, which deliver a continuous infusion, offers improvement in spasticity, ease of care and reduction in pain (29). There is conflicting evidence as to whether ITB pumps can cause progression of a scoliosis.…”
Section: Non-surgical Managementmentioning
confidence: 99%
“…Intrathecal baclofen (ITB) has been used to effectively decrease spasticity in children. Many studies have documented a significant reduction in spasticity in children who receive this treatment [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion was that ITB infusion for treatment of spasticity reduced the need for subsequent orthopedic surgery. Gooch et al reported that 31 of 80 children (39%) had orthopedic surgery during a mean follow-up time of 23 months following baclofen pump implantation [7]. Review of pre-implantation range of motion measurements indicated that orthopedic surgery would be expected in all of the patients except one.…”
Section: Introductionmentioning
confidence: 99%